Pengembangan Media Interaktif Game Quiz Berbasis Powerpoint untuk Meningkatkan Motivasi Belajar Sejarah Siswa SMA - Supriadi, Hadi; Hifni Fitriah Nurjanah (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to develop an interactive quiz-based learning media using Microsoft PowerPoint and to measure its effect on students’ learning motivation in History subjects at SMA Negeri 1 Jalaksana. The research method employed is Research and Development (R&D) using the ADDIE model, which consists of five stages: Analyze, Design, Develop, Implement, and Evaluate. The media was developed based on needs analysis, validated by subject matter and media experts, and tested on eleventh-grade students. Data were collected through motivation questionnaires administered before and after the use of the media. The results show that the developed media was rated “highly feasible” by experts and effectively increased students’ learning motivation, as indicated by improved scores across all motivation indicators. In conclusion, the interactive quiz-based learning media is effective in supporting history learning and is suitable for use as an alternative tool to enhance student motivation.